2004
DOI: 10.1128/aac.48.9.3591-3593.2004
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Using Sodium Antimony Gluconate in Stearylamine-Bearing Liposomes against Established and ChronicLeishmania donovaniInfection in BALB/c Mice

Abstract: In this work we report the activity seen with combination therapy using sodium antimony gluconate in liposomes composed of egg phosphatidyl choline and stearylamine for elimination of Leishmania donovani parasites from the liver and spleen of BALB/c mice with established and chronic infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…Previously we showed the antileishmanial activity of PC-SA as monotherapy (2,14) as well as combination therapy (7,38). Here, the efficacy of these leishmanicidal liposomes was determined as a delivery tool, as well as in combination with PM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we showed the antileishmanial activity of PC-SA as monotherapy (2,14) as well as combination therapy (7,38). Here, the efficacy of these leishmanicidal liposomes was determined as a delivery tool, as well as in combination with PM.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier we established the leishmanicidal activity and mechanism of the cationic liposome, composed of phosphatidylcholine (PC) and stearylamine (SA), as a monotherapy (2,6,14). PC-SA in combination with other antileishmanial drugs, such as SAG and AmB, not only reduced the toxicity of the drugs but also enhanced the parasite clearance in the BALB/c model to a great extent (7,38). Moreover, beneficial immunomodulatory activities of AmB were augmented in combination with PC-SA liposomes (7).…”
mentioning
confidence: 99%
“…The highest concentrations of drugs used were 90% effective doses for the suppression of parasite infection in macrophages and nontoxic to cells (Ref. 53; D. Banerjee and N. Ali, unpublished observations). It was found that both SAG and AmB were able to downregulate the enhanced production of IL-10 stimulated by LPS in a dose-dependent manner (Fig.…”
Section: Ability Of Sag and Amb To Modulate Cytokine Production Of Humentioning
confidence: 99%
“…In the proper formulations and at the appropriate sizes, liposomes deliver drugs to the skin on the basis of the similarity of the bilayer structure of the lipid vesicles to that of the natural membrane and target the macrophages within the dermis (6, 7, 41). Several lipidbased formulations for the treatment of experimental leishmaniasis have been developed (11,19,40,45). …”
mentioning
confidence: 99%